DEVELOPMENT OF EDUCATION MODEL FOR ADVANCED CHILDREN 4-10 YEARS IN THE QUR'AN AND HADIST ON PARENTING ACTIVITIES IN TK ITBUNAYYA 7 AL-HIJRAH - Sit, Masganti; Ahkas2, Akmal Walad Ahkas2 Walad; Nisa, Khairatun (Universitas Dharmawangsa Medan, 2021)
This study aims to determine: 1) Implementation of the Development of Moral Education Models for Children Age 4-10 Years in the Al-Qur'an and Hadith in Parenting Activities at Bunayya 7 Al-Hijrah Integrated Islamic Kindergarten, 2) Steps to develop parental guidelines for Educational Models Morals of Children aged 4-10 Years in the Al-Qur'an and Hadith in Parenting Activities at the Integrated Islamic Kindergarten Bunayya 7 Al-Hijrah, 3) Implementation of Moral Education Models for Children aged 4-10 Years in the Al-Qur'an and Hadith by using parenting guide on Parenting Activities at the Integrated Islamic Kindergarten Bunayya 7 Al-Hijrah, 4) Participants' responses to the Moral Education module for Children aged 4-10 Years in the Qur'an and Hadith on Parenting Activities at the Integrated Islamic Kindergarten Bunayya 7 Al-Hijrah, 5) The results of the evaluation of Moral Education for Children Age 4-10 Years in Al-Qur'an and Hadith in Parenting Activities at Bunayya 7 Al-Hijrah Integrated Islamic Kindergarten. This research was conducted using the research and development method of R & D (Research and Development) from Borg and Gall. The analytical techniques used are qualitative and quantitative. The results showed that: 1) The implementation of moral education for children aged 4-10 years in the Qur'an and Hadith in Parenting Activities at the Integrated Islamic Kindergarten Bunayya 7 Al-Hijrah before the study was only limited to involving parents in school activities, 2) Steps -steps for developing parental guidance models for Moral Education for Children Age 4-10 Years in the Qur'an and Hadith in Parenting Activities at the Integrated Islamic Kindergarten Bunayya 7 Al-Hijrah carried out by referring to the 10 steps of Borg and Gall research, 3) Moral Education of Children Ages 4-10 Years in the Al-Qur'an and Hadith In Parenting Activities using parental guidance at the Integrated Islamic Kindergarten Bunayya 7 Al-Hijrah carried out in three stages, namely: limited trial stage, wider trial, and trial feasibility of the model (operational), participant responses to the Moral Education module for Children Age 4-10 Years in the Al-Qur'an and Hadith in Parenting Activities, namely: interesting, easy to understand, good presentation for parents and child, assisting in teaching and introducing moral education to children while at home, role-playing activities and conducting tests that have been provided, language that is easy to understand, and presentations that are systematically arranged and 5) Evaluation results on parents' knowledge, attitudes, and skills after participating in activities Moral Education of Children aged 4-10 Years in the Al-Qur'an and Hadith in Parenting Activities using parental guidance at the Integrated Islamic Kindergarten of Bunayya 7 Al-Hijrah showed a significant difference.